(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
Pitch plays an important role in many linguistic systems. It is the primary set of features which determine vowel quality distinctions as well as forming the basis for intonation and contrastive tone systems. Unfortunately, much of the literature has relied on approaches to presenting and analysing pitch data that can result in a lack of data transparency, reproducibility, and analytical robustness. These issues are easily solved through the selection of a more appropriate scale for pitch values. This study presents the issues with using raw pitch data as Hertz values some historical efforts to resolve these issues, and two more appropriate solutions than some of the more widely used systems, with a way to easily calculate these alternative systems in a short Python script.